Comparison of Commercial Health Insurance and Health Social Security in Indonesia - Mellisa, Caroline; Aspan, Henry (International Conference Epicentrum of Economic Global Framework, 2025)
The health financing system in Indonesia is organized through two main schemes, namely health social security and commercial health insurance. Health social security, which is realized through the Health Social Security Administration Agency (BPJS), is mandatory and based on the principles of mutual cooperation, non-profit, and social justice with the aim of ensuring access to health services for the entire population without discrimination. In contrast, commercial health insurance is voluntary and is organized under a civil agreement between the insurer and the participant, with the main principle of risk transfer and the calculation of individual risk-based premiums. The difference in the characteristics of the two systems causes differences in financing mechanisms, service standards, legal relations between the parties, and the claim dispute resolution process. This article aims to analyze and compare commercial health insurance and health social security in Indonesia comprehensively from a health law perspective. This study uses a normative juridical method with a legislative and conceptual approach, supported by secondary data in the form of scientific literature, previous research results, and legal provisions related to the social security and insurance system. The analysis focused on differences in legal principles, health service guarantee mechanisms, patterns of legal relations between participants, organizers, and hospitals, and their implications for patient legal protection and financing certainty for hospitals. The results of the study show that health social security emphasizes the state’s function in fulfilling the right to health and social protection, while commercial insurance emphasizes freedom of contract and business risk management. These differences have a direct impact on health service practices, especially related to financing, claims, and potential disputes. Therefore, a complete understanding of the differences between commercial insurance and health social security is important as a basis for policy formulation, increasing legal protection for patients, and strengthening legal certainty and sustainability of health service financing in Indonesia.